The Influence of Perceived Usefulness and Perceived Ease of Use on Continuance Intention with Trust as an Intervening Variable (Study of QRIS Users at Universitas Negeri Jakarta) - Robith Ali Zain Musyafa; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The present study explores the factors driving the prolonged adoption of the Quick Response Code Indonesian Standard (QRIS) specifically within the digital native demographic. From a theoretical standpoint, the research augments the Technology Acceptance Model (TAM) by incorporating Trust as a pivotal intervening mechanism. Specifically, the study elucidates the magnitude with which Perceived Usefulness and Perceived Ease of Use impel Continuance Intention both directly and through the mediation of Trust among undergraduate students at the Faculty of Economics and Business, Universitas Negeri Jakarta. Employing a quantitative explanatory architecture, the investigation utilized data solicited from 94 active students through purposive sampling protocol, with data processing executed through Partial Least Squares-Structural Equation Modeling (PLS-SEM). The empirical results indicate that the proposed model exhibits strong explanatory capacity, explaining 83.2% of the total variance observed in continuance intention. Empirically, Perceived Usefulness stands out as the dominant catalyst for ongoing usage, emphasizing the indispensable need for functional advantages to ensure user retention.